Development of efficient designs of cooking systems. I. Experimental - Joshi, J.; Pandit, A.; Patel, S.; Singhal, R.; Bhide, G.; Mariwala, K.; Devidayal, B.; Danao, S.; Gudekar, A.; Shinde, Yogesh (2012)
In the conventional cooking practice, where a pot or a pan is directly placed on a flame, the thermal energy efficiency is in the range of 10-25%. It was thought desirable to increase this efficiency up to 60% or more. The cooking systems can be of various sizes. In the developing world (85% of the worlds population), open pan cooking is largely still practiced at the family level (4-10 people) or at the community level (50-2000 people or more). The latter requirement is encountered in schools, homes for senior citizens, jails, social and/or religious centers (temples, mosques, churches), social and/or educational functions (conferences, marriages, celebrations, etc.), remand homes, etc. For these different types of final application, in the present work, cooking systems have been developed. A systematic work has has been reported regarding the effect of several parameters on thermal efficiency. The parameters include the cooker size, number of pots, size and aspect ratio of the pots, heat flux, flame size, flux-time relationship, insulating alternatives, etc. Local and global optima of the parameters have been obtained, resulting in thermal efficiency of about 70%. © 2011 American Chemical Society.